2009
DOI: 10.1590/s0100-40422009000700027
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de NO2 na atmosfera de ambientes externos e internos na cidade de Araraquara, São Paulo

Abstract: Recebido em 30/9/08; aceito em 3/4/09; publicado na web em 31/8/09 EVALUATION OF NO 2 IN THE OUTDOOR AND INDOOR ATMOSPHERES AT ARARAQUARA, SÃO PAULO. The seasonal behavior of NO 2 concentration shows a maximum occurring during sugarcane crop and this suggests that the biomass burning is significant source of emission at this time of the year. Along the day, the variation of the NO 2 showed a decrease during the increased sunlight and an increase thereafter, caused by occurrence of photochemical reactions. Meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
2
0
3
Order By: Relevance
“…furniture). 49 The International Study of Asthma and Allergies in Childhood (ISAAC) written questionnaire was applied to the same school population of this study. Information on asthma and rhinitis prevalence, as well the risk factors related to these respiratory diseases, can be found in ref.…”
Section: Resultsmentioning
confidence: 99%
“…furniture). 49 The International Study of Asthma and Allergies in Childhood (ISAAC) written questionnaire was applied to the same school population of this study. Information on asthma and rhinitis prevalence, as well the risk factors related to these respiratory diseases, can be found in ref.…”
Section: Resultsmentioning
confidence: 99%
“…O extrato foi filtrado em membrana de 0,22 μm (Millipore ® ). Os íons nitrato, produto da reação entre o reagente de impregnação e o ozônio, 18 …”
Section: Extração E Análise Das Amostrasunclassified
“…Em Araraquara, município localizado na maior região produtora de cana-de-açúcar do estado de São Paulo, 1 existem importantes estudos que avaliaram a concentração de NOx, 6,18 ozô-nio 6,19 e compostos carbonílicos da queima pré corte, 10 entretanto, os níveis de ozônio e COV ainda não foram avaliados conjuntamente nessa região. Por isso, considerando a iminente mudança do cenário de emissões atmosféricas da agroindústria canavieira no Estado de São Paulo e seu potencial de emissão de poluentes atmosféricos, o objetivo deste estudo foi de avaliar as concentrações de ozônio troposférico e Compostos Orgânicos Voláteis em área com influência de emissões da agroindústria de cana-de-açúcar.…”
Section: Introductionunclassified
“…Studies in Araraquara, Brazil, showed that the NO 2 concentration in a residential kitchen with a gas stove reached 198 ppb (372 μg m −3 ). In an industrial kitchen, the concentration of NO 2 reached about 57 ppb (107 μg m −3 ), and in an indoor supermarket parking, the average value was 75 ppb (141 μg m −3 ) (Ugucione et al 2009 ). Children are more susceptible to respiratory disease and more vulnerable to ambient pollution.…”
Section: Introductionmentioning
confidence: 99%